The Effect of Extra Judicial Settlement in Criminal Cases Based on the Principle of Ultimum Remedium - Sulistiani, Lies; Fakhriah, Efa Laela (Faculty of Law, Universitas Padjadjaran, 2023)
The principle of ultimum remedium suggests that criminal sanctions should be used as a last resort when other legal avenues have been exhausted. The principle is not explicitly stated in the Indonesian Criminal Procedure Law and is often considered a mere slogan in practice. Recently, there has been a growing trend of resolving minor criminal cases outside the formal judicial process. Instead of imposing criminal penalties, conciliation or restorative justice methods are being used. In this context, restorative justice involves reaching an agreement that resolves conflict between the offender and victim. Although not specifically regulated by the Criminal Procedure Law, there has been a shift in how criminal law enforcement views minor cases, allowing for reconciliation or peace agreements. The introduction of restorative justice mechanisms by law enforcement agencies has made the practice of reconciliation more flexible, moving away from its initially punitive nature. Additionally, including peace within restorative justice indirectly strengthens the ultimum remedium principle, ensuring that criminal sanctions are truly used as a last resort in certain minor cases.DOI: https://doi.org/10.22304/pjih.v10n3.a1